Severe Hyperlipidemia Induced Hemorrhagic Pancreatitis during Pregnancy - Karen L. Koscica; Uzoma Nwaubani; Munir Nazir; Martin Gimovsky (Obstetrics and Gynecology International)
Background. We report a case of familial hyperlipidemia in pregnancy that resulted in hemorrhagic pancreatitis. Case. A patient at 27-week gestation was admitted for recurrent pancreatitis secondary to severe hyperlipidemia. With conservative care, the patient improved but on the fourth day of admission she experienced a sudden onset of hypotension and was diagnosed with hemorrhagic pancreatitis. Conclusion. Pancreatitis caused by hyperlipidemia is an uncommon event during pregnancy. A familiarity with the severe complications associated with this potentially life-threatening condition is important.